THE EFFECTIVENESS OF A TRAINING PROGRAM ACCORDING TO THE THEORY OF COMPETENCIES ADOPTED IN THE COMPETENCIES OF THE STUDENT / TEACHER OF TEACHING SCIENCES AT THE COLLEGE OF BASIC EDUCATION - Prof. Dr. Yousif Faleh Muhammad Al-Saadi, Hamsa Essam Abdul Rahman Sheikh Zahir (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of the current research is to identify the effectiveness of a training program according to the theory of competencies adopted in the competencies of the student / teacher of teaching sciences at the College of Basic Education, by verifying the validity of the following null hypothesis: 1- There is no statistically significant difference at the level of significance (0.05) between the average grades of students - teachers in the experimental group who have undergone the proposed training program and the average scores of students-teachers who did not undergo it in the measure of teaching performance. The researcher approved the experimental design with partial control for the experimental and control groups and the post-test (note card) for each of the teaching competencies of the students - teachers, while the control group did not undergo this program. The society was limited to (189) male and female students by (49 Department of Chemistry, 40 Department of Biology and 40 Department of Physics, the research and its sample on students - teachers from fourth grades / Department of Science / Life Sciences Branch - Chemistry Branch / College of Basic Education / Al-Mustansiriya University, as the number of samples reached Research (89) male and female students for the academic year 2019-2020 AD, and by random selection. The students of the Department of Chemistry (experimental group) were selected and their number reached 49 students who underwent the program and students of the Department of Biology (the control group) and their number reached 40 students. Scores of previous information test for science teaching methods and general teaching method scores for the previous academic year (2018-2019). For one sample, the effect equation, and the variance, the researcher trained the students of the two groups and identified the material represented in (the nature of science, educational goals, planning, teaching methods, scientific questions and Mock puzzles, classroom management, and tests) and the behavioral objectives were identified within the area of Bloom's classification and there were about 124 behavioral objects in order to implement the plans and training operations.